KETERAMPILAN BERBICARA BAHASA INGGRIS MAHASISWA JURUSAN MANAJEMEN AKOMODASI PERHOTELAN STIPAR TRIATMA JAYA - System, Administrator; Julyanti Paramita Sari, Ni Luh Komang; Agus Prayogi, Putu (Sphota : Jurnal Linguistik dan Sastra, 2017)
ABSTRACT   Bali is always trying to improve itself in aspects of tourism especially in accommodation and services. In terms of service to tourists, communication is one of the most decisive factors. It encourages workers in tourism sector to have good communication skills, especially communication in English. This phenomenon requires the graduates in education and training institutions of hospitality and tourism to have good communication skills, especially communication in English. In this study, the student of STIPAR Triatma Jaya majoring in Hotel Acomodation Management was raised as an object of research. The analysis in this study was made to answer the following questions: (1) the problems were faced by students in speaking English in terms of pronunciation (phonology), and (2) to find some factors in hibiting students in learning to speak. Aim of this study is to improve learning quality of English speaking ability. Primary data and secondary data were used as the data source. Data collection was taken by doing observation in research location, and descriptive qualitative technique was used to analyse the data.  This research showed that students majoring in the Hotel Acomodation Management experienced problems during the lesson especially in communicate English pronounciation, it is still influenced by the magnitude ofthe first language or mother tongue. Some factors have limited the students in speaking English, those factors are: components of linguistic mastery, and mastery of the content component, and environmental conditions during the learning process for example, the conditions where there was a little open space in the class room resulting the inclusion of sounds that interfere the process of learning. Keywords: speaking, phonology ,pronunciation, barriers, foreign language(English).